1999
DOI: 10.1086/307642
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Formation on Astrophysically Relevant Surfaces

Abstract: Recent experimental results about the formation of molecular hydrogen on astrophysically relevant surfaces under conditions close to those encountered in the interstellar medium are analyzed using rate equations. The parameters of the rate equation model are fitted to temperature-programmed desorption curves obtained in the laboratory. These parameters are the activation energy barriers for atomic hydrogen diffusion and desorption, the barrier for molecular hydrogen desorption, and the probability of spontaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
486
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(516 citation statements)
references
References 21 publications
27
486
3
Order By: Relevance
“…While that can be the case, our data show that different functionals may play a significative role in changing the physisorption value, which imposes some caution when using DFT for computing very weak interactions in open-shell systems. The computed value of the kinetic barrier for H jump between physisorbed sites resulted in 4.1 kcal mol -1 (Table 3), much higher than the experimental datum reported by Katz et al 43 of only 0.57 kcal mol -1 . Goumans et al 21 computed a value of 1.6 kcal mol -1 while Kerkeni and Bromley 17 a range between 0.14 -4.8 kcal mol -1 as a function of the considered path on the heterogeneous cluster surface.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…While that can be the case, our data show that different functionals may play a significative role in changing the physisorption value, which imposes some caution when using DFT for computing very weak interactions in open-shell systems. The computed value of the kinetic barrier for H jump between physisorbed sites resulted in 4.1 kcal mol -1 (Table 3), much higher than the experimental datum reported by Katz et al 43 of only 0.57 kcal mol -1 . Goumans et al 21 computed a value of 1.6 kcal mol -1 while Kerkeni and Bromley 17 a range between 0.14 -4.8 kcal mol -1 as a function of the considered path on the heterogeneous cluster surface.…”
Section: Resultscontrasting
confidence: 56%
“…It can be shown that the E(T) is less than 0.05 kcal mol -1 (2 meV, 20 K) while RT is 0.02 kcal mol -1 (1 meV, 10 K) at 10 K and ten times higher at T = 100 K. Using data from Table 1 we arrive at our best estimate of Hd = 1.8 kcal mol -1 (900 K) at the experimental temperature of 10 K. The datum obtained from the experimental TPD measurements 43 is 318 K, three times smaller than our best estimate. Modeling studies described in the introduction section report data which are also higher than the experimental datum.…”
Section: Resultsmentioning
confidence: 76%
“…2e). Here, we consider nH = 2 × 10 4 cm −3 and corresponding values of Tgas and AV are chosen according to (Katz et al (1999) for olivine) (Katz et al (1999) for amorphous) (Lipshtat, Biham & Herbst 2004) 2d show the progressive increment of deuterium fractionation in comparison to the non-deuterated case (Fig. 2a).…”
Section: Composition Of Grain Mantles With Deuterated Speciesmentioning
confidence: 99%
“…In the simulations presented below, the density of adsorption sites was s = 5 × 10 13 (sites cm −2 ), the activation energies were E 0 = 22 meV for diffusion and E 1 = 32 meV for desorption. These parameters are rounded values of the experimental results for hydrogen recombination on silicates [52].…”
Section: A Rate Equationsmentioning
confidence: 99%